Avaliação dos impactos ambientais de um amplificador óptico EDFA por meio da ACV: estudo sobre a fase de uso e consumo energético - Pereira, Amanda Belchior [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This research project aims to evaluate the respective environmental impacts caused by the phase of using an optical amplifier to erbium-doped fiber (EDFA) using the Brazilian energy matrix, that is, hydroelectric. First, a functional unit for EDFAs was proposed to later assess the environmental impacts of this device in its use stage. Through the application of Life Cycle Assessment (LCA) and based on ISO 14040 (2009), the main environmental impacts caused in the phase of use of the optical amplifier were identified and quantified according to the power consumed, as well as the differences in the power consumed in the different EDFA amplifiers on the market. The main contributions of this work are the identification of the aggregate power per channel as a functional unit for the research object and the quantification of the energy consumption of the optical amplifier, in order to assess the environmental impacts using the methods CML 2001, Environmental Footprint 2.0, ReCipe 2016 and TRACI.

Este projeto de pesquisa visa avaliar os respectivos impactos ambientais causados pela fase de uso de um amplificador óptico à fibra dopada com érbio (do inglês Erbium Doped Fiber Amplifiers , EDFA) utilizando a matriz energética brasileira, ou seja, hidroelétrica. Primeiramente, foi proposto uma unidade funcional para EDFAs para posteriormente, avaliar os impatos ambientais deste dispositivo na sua etap a de uso. Por meio da aplicação da Avaliação do Ciclo de Vida (ACV) e com base na ISO 14040 (2009), foram identificados os principais impactos ambientais causados na fase de utilização do amplificador óptico e quantificá los em função da potência consumida , bem como as diferenças na potência consumida nos diferentes amplificadores EDFA do mercado. As principais contribuições deste trabalho é a identificação da potência agregada por canal como unidade funcional para o objeto de pesquisa e a quantização do co nsumo energético do amplificador óptico, de forma a avaliar os impactos ambientais utilizando os métodos CML 2001, Environmental Footprint 2.0, ReCipe 2016 e TRACI.
Assessment of the environmental impacts of an optical amplifier EDFA through LCA: study on the use and consumption phase energetic
Keywords: Ciclo de vida do produto; Comunicações ópticas; Óptica; Telecomunicações